2006 IEEE International Conference on Evolutionary Computation
DOI: 10.1109/cec.2006.1688623
|View full text |Cite
|
Sign up to set email alerts
|

Improving Feature Subset Selection Using a Genetic Algorithm for Microarray Gene Expression Data

Abstract: Microarray data usually contains a huge number of genes (features) and a comparatively small number of samples, which make accurate classification or prediction of diseases challenging. Feature selection techniques can help us identify important and irrelevant (unimportant) features by applying certain selection criteria. However, different feature selection algorithms based on various theoretical arguments often produce different results when applied to the same data set. This makes selecting an optimal or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…This was followed by a hierarchical grouping of the genes selected, after which an analysis was carried out using the classification algorithms C4.5, KNN, NB and SVM. The hybrid approach used by Tan et al [ 61 ] involved a feature selection enhancement of a sample of genes using a GA; this was achieved by combining the best results from a group of feature selection methods, after which SVM were used to analyse the data. Kim and Cho [ 62 ] classified genes by employing an evolutionary neural network, while Mohamad et al [ 19 ] made their selection of genes from microarray data, using a Cyclic-GASVM hybrid method.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…This was followed by a hierarchical grouping of the genes selected, after which an analysis was carried out using the classification algorithms C4.5, KNN, NB and SVM. The hybrid approach used by Tan et al [ 61 ] involved a feature selection enhancement of a sample of genes using a GA; this was achieved by combining the best results from a group of feature selection methods, after which SVM were used to analyse the data. Kim and Cho [ 62 ] classified genes by employing an evolutionary neural network, while Mohamad et al [ 19 ] made their selection of genes from microarray data, using a Cyclic-GASVM hybrid method.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…MYOSIN HEAVY CHAIN, NONMUSCLE (Gallus gallus) [55], [56], [52], [57], [58], [59], [60], [38], [61] M76378 Human cysteine-rich protein (CRP) gene, exons 5 and 6.…”
Section: R87126mentioning
confidence: 99%
“…[60], [47], [66], [52], [49], [67], [68], [69] H43887 COMPLEMENT FACTOR D PRECURSOR (Homo sapiens) [56], [57], [58], [59] Un total de cinco genes relevantes han sido seleccionados de la base de cáncer de pulmón. La selección de estos genes se debe a que el clasificador logro separar correctamente la información contenida en la base de datos, esto significa que el clasificador ha logrado separar la clase Malignant Pleural Mesothelioma (MPM) de la clase Adenocarcinoma (ADCA).…”
Section: M63391unclassified
“…In order to estimate the performance of the proposed method, we applied our method on University of California-Irvine (UCI) machine-learning data sets [14]. Experimental results showed that our method is effective and efficient in finding small subsets of the significant features for reliable classification.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluate the fitness values of all individuals in the population using a classifier to evaluate each chromosome (the selected feature subset) based on the classification accuracy and the dimension of the feature subset. Tan et al [14] proposed the following fitness function in order to optimize two objectives: maximize the classification accuracy of the feature subset and minimize the size of the feature subset.…”
mentioning
confidence: 99%